Diversity, bioactivity, and secondary metabolite profiles of bacteria isolated from different tissues of the mollusk gastropod truncatella sp - Flores, Malem S.; Ibana, Joyce A. (Quezon City Institute of Biology, College of Science, University of the Philippines Diliman, 2015)
The emergence of drug resistance for many diseases has been for decades the driving force behind the pursuit of naturally-occuring bioactive compunds. Among the candidate drug leads, marine sources are one of the most promising, owing to the vast biodiversity of marine organisms. However, marine gastropods with shells are an overlooked source of bioactive secondary metabolites because they are well-protected by their shell covering and some produce venom. In this study, several bacteria were isolated from different tissues or Truncatella sp., a small gastropod mollusk that is found on land very close to seawater (splash zone). Identification of each isolate using 16S sequence analysis revealed a diversity of Gram-negative and Gram-positive bacteria, with Actinobacteria as the dominating group. Furthermore, secondary metabolites produces by Truncatella-associated bacteria showed promising antimicrobial and anti-cancer properties. Some of these bioactive metabolites manifested narrow spectrum antimicrobial activity against Staphylococcus aureus or Pseudomonas aeruginosa which having weak inhibitory effect on lactic acid bacteria commensals. Likewise, there were extracts that exhibited selective cytotoxic activity on the lung cancer cell line, A549 or colorectal cancer cell, HCT 116, with moderate or no cytotoxicity on the normal kidney cell line, MDCK. Chemical profiles of secondary metabolites determined by reverse-phase high performance liquid chromatography (RP-HPLC) demonstrated common and unique patterns of metabolites for each isolate. This suggests that Truncatella is a potential source of bioactive metabolite-producing bacteria, which can be valuable for drug discovery and that secondary metabolite profiles may present distinct phenotypic traits of the microorganisms. Importantly, this is the first study to report on the genetic and chemical profile diversity of bacteria associated with Truncatella, and their corresponding antimicrobial and anticancer properties.
Thesis (Master of Science in Microbiology)--University of the Philippines Diliman
Keywords: Bacteria -- Identification; Mollusk culture; Cancer -- Treatment